2019
DOI: 10.21037/jtd.2019.03.41
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcome and hemodynamic performance of St. Jude Trifecta aortic prosthesis: short-term follow-up and risk factors analysis

Abstract: Background: We retrospectively analysed the short-term outcome of the third-generation St. Jude Trifecta aortic prosthesis. Methods: Between December 2014 and December 2017, 177 patients (mean age 75.1±6.8 years, 95 males, 82 females) underwent aortic valve replacement with a St. Jude Trifecta aortic prosthesis and were followed up to 27±9 months. Preoperatively 92 patients (52.0%) were in NYHA class III-IV, EuroSCORE II was 3.2%±2.1%. Results: Trifecta sizes implanted were 19 mm (n=46) (26%), 21 mm (n=69) (39… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 50 publications
0
6
0
Order By: Relevance
“…Several studies presented favourable hemodynamics with St. Jude Trifecta in the AV position and considered it as the best option for AVR surgery. 28,29 Moreover, resting and exercise hemodynamics of the stented St. Jude Trifecta were similar to that of the stentless Medtronic Freestyle valve. 30 In a systematic review and meta-analysis by Phan et al, 31 attention was focused on the favourable mean gradient and EOA of this valve.…”
Section: Discussionmentioning
confidence: 64%
“…Several studies presented favourable hemodynamics with St. Jude Trifecta in the AV position and considered it as the best option for AVR surgery. 28,29 Moreover, resting and exercise hemodynamics of the stented St. Jude Trifecta were similar to that of the stentless Medtronic Freestyle valve. 30 In a systematic review and meta-analysis by Phan et al, 31 attention was focused on the favourable mean gradient and EOA of this valve.…”
Section: Discussionmentioning
confidence: 64%
“…This promising performance has increased its approval, with a resultant popularity in usage. More large studies have also proved comparable or slightly lower rates of mortality and congestive heart failure, supporting the consensus surrounding the Trifecta [9,[12][13][14]. However, a Trifecta mid-term data analysis reports contradictory outcomes.…”
Section: Introductionmentioning
confidence: 73%
“…We speculate that the low PPM rate might be related to the excellent hemodynamic conditions afforded by the widely-used St Jude Trifecta valve, which was used in more than 70% of the patients. Several studies have suggested that the St Jude Trifecta valve shows favorable hemodynamics and is the best option for the aortic valve position [9,22,23]. In a systematic review and meta-analysis by Phan et al, particular attention was paid to the favorable mean gradient and EOA obtained with the Trifecta valve [24].…”
Section: Ppm Ratementioning
confidence: 99%